The Influence of Accounting and Auditing Expertise in the Audit Committee on the Risk of Financial Statement Fraud: A Study on Mining and Energy Sector Companies Listed on the IDX in 2020-2024 - Rachmawati, Nucke Mariant; Kusumaningsih, Ambar (PT Keberlanjutan Strategis Indonesia, 2026)
Finding out how energy and mining companies listed on the Indonesia Stock Exchange fare in terms of audit committee accounting, auditing expertise, and financial statement fraud from 2020 to 2024 is the main goal of this study. You can tell whether an audit committee is competent if its members are certified professionals or if they have extensive knowledge of financial issues. When evaluating a company's financial statements for indicators of fraud, the Beneish M-Score is a useful tool. This research makes use of quantitative methods and secondary data collected from the company's books and yearly reports. To carry out the sampling procedure, the purposive sample strategy was utilized, using preset criteria. With the help of IBM SPSS software version 29, the data analysis method made use of multiple linear regression. According to the study's findings, having competent auditors and accountants on the audit committee greatly reduces the possibility of financial reporting fraud. In addition, debt and business size have a favorable effect on M-Score, whereas profitability has a considerably negative effect. All of the model's variables were considerably impacted simultaneously, as shown by a determination coefficient value (R²) of 0.918. Findings indicate that energy and mining companies may reduce their risk of financial reporting fraud by establishing an audit committee with sufficient accounting and auditing expertise.